Prognostic Signature and Tumor Immune Landscape of N7-Methylguanosine-Related lncRNAs in Hepatocellular Carcinoma - Wei, Wei; Liu, Chao; Wang, Meng; Jiang, Wei; Wang, Caihong; Zhang, Shuqun (Frontiers in Genetics, 2022)
Despite great advances in the treatment of liver hepatocellular carcinoma (LIHC), such as immunotherapy, the prognosis remains extremely poor, and there is an urgent need to develop novel diagnostic and prognostic markers. Recently, RNA methylation-related long noncoding RNAs (lncRNAs) have demonstrated to be novel potential biomarkers for tumor diagnosis, prognosis as well as immunotherapy response, such as N6-methyladenine (m6A) and 5-methylcytosine (m5C). N7-methylguanosine (m7G) is a widespread RNA modification in eukaryotes, but the relationship between m7G-related lncRNAs and prognosis of LIHC patients as well as tumor immunotherapy response is still unknown. In this study, based on the LIHC patients’ clinical and transcriptomic data from TCGA database, a total of 992 m7G-related lncRNAs that co-expressed with 22 m7G regulatory genes were identified using Pearson correlation analysis. Univariate regression analysis was used to screen prognostic m7G-related lncRNAs, and the least absolute shrinkage and selection operator (LASSO) and multivariate Cox regression was applied to construct a 9-m7G-related lncRNA risk model. The m7G-related lncRNA risk model was validated to exhibit good prognostic performance through Kaplan-Meier analysis and ROC analysis. Together with the clinicopathologic features, the m7G-related lncRNA risk score was founded to be an independent prognostic factor for LIHC. Furthermore, high-risk group LIHC patients was unveiled to have higher tumor mutation burden (TMB), their tumor microenvironment was more prone to the immunosuppressive state and exhibit lower response rate to immunotherapy. In addition, 47 anti-cancer drugs were identified to exhibit difference in drug sensitivity between the high-risk and low-risk groups. Taken together, the m7G-related lncRNA risk model might display potential value in predicting prognosis, immunotherapy response and drug sensitivity in LIHC patients.